Mewujudkan Sekolah Ramah Lingkungan di Sekolah Menengah Atas Negeri 1 Kuala Kabupaten Nagan Raya - Sopar, Sopar; Samwil, Samwil; Abdillah, Ligar; Yulianda, Riki; Maifizar, Arfriani; Lestari, Yeni Sri; Yana, Rahma Husna; Sariyanti, Lilis; Asra, Saiful (Medan Resource Center, 2025)
This article is titled Creating an Environmentally Friendly School for Students, particularly within the environment of SMA Negeri 1 Kuala, Nagan Raya Regency, Aceh Province. The purpose of this community service is to realize an environmentally friendly school for students, especially within the environment of SMA Negeri 1 Kuala, Nagan Raya Regency, Aceh Province.The approach method used in this community service is the Focus Group Discussion (FGD) through socialization with 21 (twenty-one) students from Class XI Science at SMA Negeri 1 Kuala, Nagan Raya Regency, Aceh Province. The planned activity is in the form of a socialization session, which will be followed by a question-and-answer session, discussions, and writing practices for the participants. At the beginning of the socialization, the team presented the material using a PowerPoint presentation for 20 minutes, followed by a Q&A session and discussion for 90 minutes, and concluded with a 10-minute summary. This community service aims to create an environmentally friendly school, particularly in environmental management, to support the Go Green School program. Students, educational staff, the school committee, teachers, and the principal play an active role in each stage of the activities, including classroom explanations, planning environmentally friendly school activities such as Go Green School, and implementing the LISA (Lihat Sampah Ambil — See Trash, Pick It Up) program. All participants felt that activities like this are important and requested continuous guidance in the future due to their many benefits. Environmental management, cleanliness, and greening activities within the Go Green School program, along with their practical implementation in schools, can provide insights to students to enhance their skills and behavior in implementing environmentally friendly schools. This includes social friendliness, physical environmental friendliness, Go Green School, and Adiwiyata schools.